COORDINATES OF THE CULTURE CONSUMPTION IN URBAN ENVIRONMENT - GÂRDAN, Daniel Adrian; CĂTOIU, Iacob; GÂRDAN, Iuliana Petronela (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 18 (2016): Annales Universitatis Apulensis Series Oeconomica, 2016)
Applying marketing principles within the culture field represents a challenge addressed for specialists, taking into consideration the substantial changes that the consumption of culture has met at the end of the 20th century and the beginning of the 21st century. This approach cannot be achieved without a coherent substantiation of the ways through which actual culture consumer behavior manifest itself. The present paper aims to investigate with the help of an exploratory marketing research a number of items referring to the main coordinates of the current culture consumption from the urban Romanian environment. The research results were analyzed also from the perspective of various statistical data about the access to culture and participation of European citizens to its specific forms of expression. In the context of complex transformations that have occurred in the social, economic and implicitly cultural layer, after 1990, at the level of Romanian society, the way that Romanian culture consumers are relate to the dynamics of their own needs has been radically changed. Within the paper are proposed not only some future research directions but also different measures which at a social level can influence the evolution of culture consumption towards the reduction of disparities compared with the average of main indicators considered at European level.